Association between early childhood caries, streptococcus mutans level and genetic sensitivity levels to the bitter taste of, 6-N propylthiouracil among the children below 71 months of age - Raghavendra Pidamale; B Sowmya; Ann Thomas; Tony Jose; Kaikure Kushalappa Madhusudan; Ganesh Prasad (Wolters Kluwer Medknow Publications, 2012)
Background: Oral health is an integral component of pre-school health and well-being. Unfortunately, many children are afflicted with dental caries at an early age, even those as young as 12 months of age. The purpose of this study is to determine the association between Early Childhood Caries (ECC), Streptococcus mutans and genetic sensitivity levels to the bitter taste of, PROP among the children below 71 months of age. Materials and Methods: Total of 119 children belonging to the age group of 36 to 71 months of both sexes, were recruited from A. J. Institute of Dental Sciences, Mangalore (Karnataka). PROP sensitivity test was carried out to determine the inherent genetic ability to taste a bitter or sweet substance. One who tasted bitter as taster and one who was not able to differentiate/tasted like paper as non-tasters. Facial expression was observed during the tasting to support the verbal response. Estimation of S. mutans level and caries experience was recorded. The results were statistically analyzed using Mann'Whiteney-U Test and Kruskal value test. Results: In the total of 119 children, the mean DMFS was definitely higher in non-taster children compared to tasters and also had a high S. mutans level. Tasters had low ECC experience, low S. mutans level. The tasters had a mean DMFS value of 9.5120 (S.D. 7.0543) and non-tasters had a value of 7.7250 (S.D. 8.33147), which was statistically significant. Conclusion: Children who had higher level S. mutans had ECC and were non tasters. The PROP sensitivity test (filter paper test) proved to be a useful diagnostic tool in determining the genetic sensitivity levels of bitter taste. Age and low socio-economic status of pre-school children suggest a complex multifactorial relationship between S. mutans colonization, ECC and taste perception.